2015
DOI: 10.1111/1471-3802.12098
|View full text |Cite
|
Sign up to set email alerts
|

Using ‘voice’ to understand what college students with intellectual disabilities say about the teaching and learning process

Abstract: There is a growing awareness of the value of using pupils’ voices in educational research. At primary and second level, the principle of pupil voice has gained in profile over the last decade. However, in higher education, the use of voice in research collaborations remains under‐theorised and under‐utilised. This paper reports on an inclusive phenomenographic study undertaken with college students with intellectual disabilities (ID). It outlines how pupil voice can be used to gain a deeper understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…In recent years, there has been increasing interest in educational research in eliciting the voices of children and young people with SEND on their mainstream and special school experiences. Overall, the findings indicate that they are capable of expressing their views and feelings (Cefai and Cooper, ; O'Connor, Hodkinson, Burton, et al., ), can make pertinent suggestions for school improvement (Loyd, ), provide constructive feedback for teaching and learning (Blackman, ; Kubiak, ) and, most importantly, can contribute positively to promoting school reform and inclusive practice (Adderley, Hope, Hughes, et al., ). Cefai and Cooper (), for example, in a review of eight small‐scale qualitative studies, reported the reasons given by secondary‐aged pupils with social emotional mental health (SEMH, previously social, emotional and behavioural) difficulties for their struggle to fit into mainstream schools.…”
Section: What Do Children and Young People With Send Report About Thementioning
confidence: 99%
“…In recent years, there has been increasing interest in educational research in eliciting the voices of children and young people with SEND on their mainstream and special school experiences. Overall, the findings indicate that they are capable of expressing their views and feelings (Cefai and Cooper, ; O'Connor, Hodkinson, Burton, et al., ), can make pertinent suggestions for school improvement (Loyd, ), provide constructive feedback for teaching and learning (Blackman, ; Kubiak, ) and, most importantly, can contribute positively to promoting school reform and inclusive practice (Adderley, Hope, Hughes, et al., ). Cefai and Cooper (), for example, in a review of eight small‐scale qualitative studies, reported the reasons given by secondary‐aged pupils with social emotional mental health (SEMH, previously social, emotional and behavioural) difficulties for their struggle to fit into mainstream schools.…”
Section: What Do Children and Young People With Send Report About Thementioning
confidence: 99%
“…The students' perspectives are a key element to consider in educational research targeting the elimination of oppressive barriers, particularly regarding students with any type of disability (Higgins, 1992). Some researchers, such as Moriña (2018), Kubiak (2017); Simón, Echeita, and Sandoval (2018), not only defend the right of student to be listened to, but also justify that their opinions are relevant for the improvement of educational policies.…”
Section: Listening To the Opinions Of Students To Transform The Schoolmentioning
confidence: 99%
“… Illuminate the barriers facing disabled students and the impact they have : Denhart 2008;Hopkins 2011;Redpath et al 2013;Stein 2013; Lopez-Gavira and Morina 2015  Identify appropriate and helpful ways of reducing such barriers and inform pedagogical practices : Webster 2004;Quinlan, Bates and Angell 2012;Redpath et al 2013;Kubiak 2015;Lourens and Swartz 2016).…”
Section: Giving Voice To Disabled Students As a Political Act: Navigamentioning
confidence: 99%
“…The majority of literature that I have reviewed in preparation for writing this article uses the term 'student with a disability' (see for example Hughes et al 2016;Lopez-Gavira and Morina 2015;Kubiak 2015;Baker et al 2012;Diez et al 2015;Damiani and Harbour 2015;Argawal, et al 2014;Hurst 2015). The remaining literature uses the term 'disabled student' (see for example: Beauchamp-Pryor 2012; Wray 2012; Riddell and Weedon 2014;Berrgren et al 2016;Hargreaves et al 2014;Hutcheon and Wolbring 2012;Redpath et al 2013;Hopkins 2011;Vickerman and Blundell 2010).…”
Section: Being Sensitive To Tensions Regarding the Construction Of DImentioning
confidence: 99%